A shortage of cadavers: The predicament of regional anatomy education in mainland China. Issue 4 (12th April 2018) - Chen, Dan; Zhang, Qi; Deng, Jing; Cai, Yan; Huang, Jufang; Li, Fang; Xiong, Kun
Abstract : Both in mainland China and around the world, regional anatomy stands as one of the most important basic science courses in medical school curricula. As such, dissection of human cadavers and use of prosected specimens remains the most essential teaching method in anatomy education. However, medical educators have raised increasing concerns about an ongoing shortage of cadavers for medical use in mainland China, a problem which may seriously limit the future development of human anatomy education. Based on a survey on cadaver usage in anatomy education in mainland China, this study found that the cadaver resources of most given medical schools in mainland China are associated with their geographic location, academic ranking, and local support for body donation policies. Effective measures to alleviate this shortage of cadavers may include future efforts to promote national‐level body donation legislation, broader acceptance of body donation among Chinese citizens, and an efficient and humane protocol for body donation. Anat Sci Educ 11: 397–402. © 2018 American Association of Anatomists.